Improved extraction of peanut residues from a wheat flour matrix for immunochemical detection. (25th April 2019) - Jayasena, Shyamali; Wijeratne, Subhashinee S.K.; Taylor, Steve L.; Baumert, Joseph L.
Highlights: High pH buffers & PBS with GuHCl gives better recovery than the Veratox kit buffer. Veratox peanut ELISA recovers more peanut from minimally processed pastry samples. Better recovery of peanut from highly processed pastry samples with the Morinaga kit. An ELISA kit targeting heat stable allergens better suited for heat-processed foods. Abstract: The efficacy of different buffers in extracting peanut from a solid model food incurred with peanut and subjected to processing was evaluated using two commercial ELISA kits: Veratox® for peanut allergen and peanut ELISA from Morinaga. Average percentage recoveries of peanut from unprocessed samples using the kit supplied buffers were 46 ± 5 and 28 ± 2 with the Veratox and Morinaga kits, respectively. However, Na2 CO3, pH 9.6 and PBS containing 1 M GuHCl recovered 65% ± 4% and 77% ± 10% of peanut, respectively from unprocessed samples with the Veratox kit. These two buffers also performed better than the Veratox buffer with fried, high pressure processed, and baked samples. PBS containing SDS and β-ME, performed significantly better than the Morinaga buffer in recovering peanut from unprocessed, boiled and fried samples. Thus, the use of alternative extraction buffers provides better recovery of peanut residues from a processed solid food matrix.